2008
DOI: 10.1038/jp.2008.22
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and lipid peroxidation products in infants with hypoxic ischemic encephalopathy

Abstract: Background: Iron delocalization or misregulation of iron metabolism may play a critical role in the pathology of hypoxic ischemic encephalopathy (HIE).Objective: To study iron metabolism and lipid peroxidation in newborn infants and to correlate non-protein-bound iron (NPBI) concentration with the severity of the post-asphyxial injury and subsequent short-term outcomes.Study Design: Concentrations of NPBI and malondialdehyde (MDA) in the serum and in the cerebrospinal fluid (CSF) were measured in eight healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Moreover, metabolite levels correlated with the severity of HIE [33]. Shouman et al [34] also found increased NPBI and MDA CSF and serum levels in babies with asphyxia evolving to HIE, and established a correlation between clinical severity and metabolite concentration. Brain tissue is especially rich in lipid components in their cell membranes.…”
Section: Compoundsmentioning
confidence: 93%
“…Moreover, metabolite levels correlated with the severity of HIE [33]. Shouman et al [34] also found increased NPBI and MDA CSF and serum levels in babies with asphyxia evolving to HIE, and established a correlation between clinical severity and metabolite concentration. Brain tissue is especially rich in lipid components in their cell membranes.…”
Section: Compoundsmentioning
confidence: 93%
“…The formation of free-radicals, some being highly reactive such as hydroxyl radical, in addition to oxygen is also supported by a major haematic concentration of free iron due to hypoxia-induced acidosis that is known to detach the iron bonded in circle to transferrine [10]. These oxidative processes, in fact, can be blocked by deferoxamine, an iron-chelator that experimental studies in lambs have shown capable of preserving cortical cells membrane stability and electrocortical brain activity when used during early reperfusion after H-I insult [11].…”
Section: Mechanisms Of Cerebral Injurymentioning
confidence: 99%
“…Of note, a small pilot study has previously associated serum with CSF concentrations of LPO. 15 We did not discover data to support the similarity of LPOs in cord blood and serum samples, consequently we opted not to use cord blood samples for LPO assessment in the control group as a surrogate for serum blood concentrations. However, we spent the effort to coordinate blood sampling with other tests prescribed for their individual care whenever applicable to minimize insensitivity to these newborns.…”
Section: Discussionmentioning
confidence: 96%
“…15 To detect an increase in the asphyxia group by 20%, a sample of 38 per group will be required. To detect an extra 50% increase in LPO concentrations in non-survivors, at least 5 non-survivors within the asphyxia group will be required.…”
Section: Statistical and Power Analysismentioning
confidence: 99%